Racconto d'egitto : trascrizione e traduzione del manoscritto di ʻAbd al-Laṭīf al al-Baġdādī (con brevi note di commento) - ʻAbd al-Laṭīf al-Baghdādī, Muwaffaq al-Dīn, 1162-1231.; Kzzo, Ahmed F.,; Kzzo, Ahmed F.,; Bellucci, Nikola,; Bellucci, Nikola, (Archaeopress Archaeology, 2020)
This edition provides an Italian translation of Abd al-Laṭīf al-Baghdādī's fascinating account of Egypt in the 12th-13th centuries. The translation is accompanied by a full transcription of the original Arabic manuscript as well as essential and insightful commentary and analysis.